The Homotopy Lifting Theorem for Semiprojective $C^*$-Algebras - Blackadar, Bruce (MATHEMATICA SCANDINAVICA, 2016)
We prove a complete analog of the Borsuk Homotopy Extension Theorem for arbitrary semiprojective $C^*$-algebras. We also obtain some other results about semiprojective $C^*$-algebras: a partial lifting theorem with specified quotient, a lifting result for homomorphisms close to a liftable homomorphism, and that sufficiently close homomorphisms from a semiprojective $C^*$-algebra are homotopic.